Analyzed Question Quality of School Examinations Class IX Science Subjects - Maiyusri Eka Putri; Syamsurizal Syamsurizal; Lufri Lufri (Bioeducation Journal, 2022)
The quality of the items on the instrument affects the results of the class IX students' school exams. As an evaluator, the teacher has not conducted an analysis of the school exam questions. Therefore, it is not known the quality of the items and the accuracy of the students' test results. This is evidenced by the low results of school exams in the last three years. The Circular of the Minister of Education and Culture regarding the elimination of the National Examination, requires teachers in each Education Unit to make quality questions. Quality questions were identified by analyzing the items. This study aims to analyze the quality of the school exam items given to class IX SMP students. The quality of the items analyzed was based on the aspects of validity, reliability, level of difficulty, distinguishing power and quality of distractors. This type of research is a descriptive study. The population is all answer sheets of students who take the Science Subject School Examination of SMP Negeri 1 Lengayang in the academic year 2020/2021, totaling 232 copies. Samples were taken by simple random sampling technique and obtained 100 copies. The type of data is secondary data and data collection using the documentation method. Quantitative data analysis used Anates version 4.0.9. Based on the results of the analysis, it was found that the validity of the items was low with an xy correlation of 0.48, high reliability with a value of 0.65, good distinguishing power with good criteria of 36.7%, moderate difficulty level with moderate criteria 66.7%, and the quality of the distractor is not good with less good criteria 30.7%. In conclusion, the quality of the grade IX school examination items in science subjects at SMP Negeri 1 Lengayang in the academic year 2020/2021 is not yet a good criterion.